2021
DOI: 10.1371/journal.pone.0256704
|View full text |Cite
|
Sign up to set email alerts
|

Identification and in-silico characterization of taxadien-5α-ol-O-acetyltransferase (TDAT) gene in Corylus avellana L.

Abstract: Paclitaxel® (PC) is one of the most effective and profitable anti-cancer drugs. The most promising sources of this compound are natural materials such as tissue cultures of Taxus species and, more recently, hazelnut (Corylus avellana L.). A large part of the PC biosynthetic pathway in the yew tree and a few steps in the hazelnut have been identified. Since understanding the biosynthetic pathway of plant-based medicinal metabolites is an effective step toward their development and engineering, this paper aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…In addition, it was revealed that hazel cell extract inhibited the growth of cancer cells, which was attributed to paclitaxel and similar compounds (Bemani et al 2013). Recently, the biosynthetic pathway of this important molecule in hazel has been taken into consideration as a step towards its development and engineering (Raeispour Shirazi et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was revealed that hazel cell extract inhibited the growth of cancer cells, which was attributed to paclitaxel and similar compounds (Bemani et al 2013). Recently, the biosynthetic pathway of this important molecule in hazel has been taken into consideration as a step towards its development and engineering (Raeispour Shirazi et al 2021).…”
Section: Introductionmentioning
confidence: 99%